Establishment and Application of the Void Closure Prediction Model of 316LN - Min Qin; Jiansheng Liu; Jingdan Li (Advances in Materials Science and Engineering)
The presence of voids in the ingot affects the mechanical properties of the final products of the forging process. It is essential to establish a void closure model to predict cavity closure in the forging process to optimize the forging process and improve forging quality. The main purpose of this study is to obtain an accurate prediction model of void closure for 316LN stainless steel. Using the FEM simulation method to study the closure of spherical voids during forging compression of 316LN materials, we can accurately characterize the state of void closure. The void closure ratio K under different deformations at 1,200°C was counted, and the relationship between K and the effective strain was established to obtain the void closure prediction model of 316LN stainless steel. The void closure prediction model is implanted into DEFORM software through the secondary development method to generate the void closure ratio K. In the postprocessing module of DEFORM software, the void closure status of each part during the forming process can be directly observed. Comparing the results of large-scale upsetting experiments and simulation results, the closure error of each part was only 3%, which indicates that the void closure model established in this paper has higher accuracy, which is helpful for the optimization of the forging process and the control of forging quality.